Thursday

December 18, 2014

December 18, 2014

Posted by **Jill** on Saturday, November 25, 2006 at 11:57pm.

IF f(x) = ln (1-x)

Then use the chain rule with u(x) = 1-x

f(u) = ln u

df/dx = df/du du/dx

f'(x) = -1/(1-x)

Use the chain rule again:

f"(x) = -[-1/(1-x)^2]*(-1) = -1/(1-x)^2

What is the pattern there how can you give an expression for f ^(n) (x) [the n-th derivative of f(x)]?

**Answer this Question**

**Related Questions**

Math - Calculus Question. - hey can someone explain to me the relationship ...

Calculus - How do I use the chain rule to find the derivative of square root(1-x...

Calculus - Use implicit differentiation to find dy/dx. e^4x = sin(x+2y). This is...

Implicit Differentiation - Find the slope of the tangent line to the curve (a ...

calculus - Find dz/dy and dz/dx Let z = ∫e^(sin(t))dt from x to y a = x b...

MoRe HeLp PlEaSe!! (calc) - Also can I get some help with this LONG, TIRESOME ...

Implicit Differentiation - Use implicit differentiation to find the slope of the...

calculus - Let z = ∫e^(sin(t))dt from x to y a = x b = y I tried thinking ...

calculus - Let z = ∫e^(sin(t))dt from x to y a = x b = y I tried thinking ...

calculus - Let z = ∫(e^sin(t)dt) from x to y a = x b = y I tried thinking ...